2012
DOI: 10.1186/1471-230x-12-148
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 reverses chronic pancreatitis-induced mechanical allodynia, phosphorylation of NMDA receptors, and cytokines expression in the thoracic spinal dorsal horn

Abstract: Background: We previously reported that immune activation in the spinal dorsal horn contributes to pain induced by chronic pancreatitis (CP). Targeting immune response in the CNS may provide effective treatments for CP-induced pain. Recent findings demonstrate that resolvin D1 (RvD1) can potently dampen inflammatory pain. We hypothesized that intrathecal injection of RvD1 may inhibit pain of CP. Methods: Rat CP model was built through intrapancreatic infusion of trinitrobenzene sulfonic acid (TNBS). All the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…Along these lines, RvD1 (100 ng/kg) decreases TNBS-induced mechanical allodynia and blocked cytokine production in spinal dorsal horn (Quan-Xin et al 2012), and RvD2 (0.01-1 ng) prevents formalin-induced pain. As part of the molecular mechanisms, RvD2, RvE1, and RvD1 differentially regulated transient receptor potential (TRP) channels (Park et al 2011).…”
Section: New Uses Of Spms In Animal Disease Modelsmentioning
confidence: 87%
“…Along these lines, RvD1 (100 ng/kg) decreases TNBS-induced mechanical allodynia and blocked cytokine production in spinal dorsal horn (Quan-Xin et al 2012), and RvD2 (0.01-1 ng) prevents formalin-induced pain. As part of the molecular mechanisms, RvD2, RvE1, and RvD1 differentially regulated transient receptor potential (TRP) channels (Park et al 2011).…”
Section: New Uses Of Spms In Animal Disease Modelsmentioning
confidence: 87%
“…The dorsal spinal cord then acts as an important pain modulation center, as it provides a place for the brainstem descending suppression system to execute its action and also regulates the transmission of nociceptive information through the intermediate neurons (Singh and Tao 2012;Takazawa and MacDermott 2010;Yang and Ma 2011). Many studies have shown that a large amount of pain-associated molecules act in the dorsal spinal cord, especially those associated with nerve pathological pain (Quan-Xin et al 2012;Wei et al 2013;Xie et al 2012;Zhu et al 2013). Besides, various neurotransmitters and neurotransmitter receptors in the dorsal spinal cord could be altered during the nerve pathological pain (Paul et al 2012;Rahman et al 2007;Wan et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Spinal administration of RvE1 reduced capsaicin‐ and tumor necrosis factor (TNF)–induced spontaneous pain and hypersensitivity in mice and partially attenuated pain behavior in models of neuropathic pain 20. RvD1 and RvE1 can modulate TRPV‐1 and TNF responses in the spinal cord 20, 21, 22 and inhibit phosphorylation of N ‐methyl‐ d ‐aspartate receptors and cytokine expression in the spinal cord in the setting of chronic pancreatitis‐induced pain 23. Thus, both peripheral and spinal mechanisms of action contribute to the inhibitory effects of the resolvins in models of inflammatory and neuropathic pain, with predominant peripheral antiinflammatory mechanisms including inhibition of neutrophil infiltration, edema, and proinflammatory cytokine expression 21.…”
mentioning
confidence: 99%